STUDI PENDIDIKAN ISLAM DI SMA MUHAMMADIYAH AMBON - Borut, Ismail (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
Study is an activity of learning, scientific study to gain knowledge. Study can also be done by reading, investigating, the process in this context is Islamic education. The educational institution of SMA Muhammadiyah Ambon is a center for learning and development of human resources in science and technology for the community in the city of Ambon. SMA Muhammadiyah Ambon is in the form of a pesantren because it has its own characteristics compared to other public and private schools in the city of Ambon. This study uses a qualitative descriptive approach and library research or library research. Descriptive research is research that is intended to describe and analyze phenomena, events, social activities, facts, characteristics and relationships between phenomena that are owned about the Study of Islamic Education at SMA Muhammadiyah Ambon. In this study of Islamic education studies at SMA Muhammadiyah Ambon, structured interview techniques, passive participant observation and documentation can be used and conducting research data analysis. Muhammadiyah High School Ambon has two Islamic education learning curricula, namely from the Department of Education and Culture on Islamic education and the Muhammadiyah Elementary, Middle and Non-Formal Education Council (Dikdasmen NF) on Al-Islam and Muhammadiyah. These two educational curricula are collaborated in learning at Muhammadiyah High School Ambon. Islamic education is guidance given by someone to someone so that they develop optimally with Islamic teachings in order to form a human being with a Muslim personality based on the values of Islamic teachings based on the Qur'an and Sunnah.